Bystanders’ Victim Blaming and Minimizing Consequences of Weight-Based Cyberhate Attacks: The Roles of anti-Fat Attitudes, Body-Positive Online Content, and Gender - Bedrosova, Marie (Journal of interpersonal violence, 2023)
Physical appearance and, specifically, weight are common reasons for cyberhate attacks among adolescents. Using a between-subject experimental design, this study focuses on the bystanders of such attacks on Instagram. We investigate bystanders’ assessments in the form of two moral disengagement (MD) mechanisms—victim blaming and minimizing consequences—and we compare the assessments of attacks that are diversified by the victim’s weight (i.e., a victim who is plus-size and a victim who is thinner). We also examine the moderating roles of bystanders’ prejudice against people who are plus-size in the form of the so-called anti-fat attitudes, their frequency of viewing body-positive online content, and gender. The study’s data come from an online survey conducted in 2020 with a representative sample of 658 Czech adolescents, aged 13–18. We tested our hypotheses with structural equation modeling. The results show that the two MD mechanisms work differently. The victim’s displayed weight affected the bystanders’ tendency to victim blame: adolescents blamed the victim who is plus-size more than the victim who is thinner, but the victim’s weight made no difference in minimizing the consequences of the incident. A moderating effect for anti-fat attitudes and gender was found for victim blaming. Bystanders with higher anti-fat attitudes and boys blamed the victim who is plus-size more than the victim who is thinner. On the other hand, there was no effect for the frequency of viewing body-positive online content for either of the MD mechanisms. The results are discussed with regard to the differences between the two mechanisms and the practical implications for educational and prevention programs for youth.